Experimental analisys on Escherichia coli viability in salt water - Vieira, Regine Helena Silva dos Fernandes; Silva, Ana Isabel Mota; de Sousa, Oscarina Viana; Hofer, Ernesto; Vieira, Gustavo H. F.; Sampaio, Silvana Saker; de Lima, Elenice Araújo (Arquivos de Ciências do Mar, 2017)
Five experiments were carried out in order to investigate the resistance of Escherichia coli strains isolated from Cocó River and inoculated in sea water, stored in laboratory at environmental temperature. The strains of E. coli were incubated at 37 and 44.5 o C. The initial inocule (Ti) was of 166 x 109 CFU/ml. The time of each experiment was 168 h. Sea water resistant strains were counted at T0 (time which the inocule was introduced into the sea water), T1, T2, T24, T120 and T168h. Up to 168 h, for all experiments, it was possible to detect viable strains of E. coli. There was no statistically significantly difference (α = 0.05) between experiments, considering the strains were isolated from the same place and were treated on the same manner. Other factors, such as UV rays, may be more deleterious to the cell than salt concentration in sea water itself.